2021
DOI: 10.1016/j.tibs.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid-Based Technologies Targeting Coronaviruses

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently creating a global health emergency. This crisis is driving a worldwide effort to develop effective vaccines, prophylactics, and therapeutics. Nucleic acid (NA)-based treatments hold great potential to combat outbreaks of coronaviruses (CoVs) due to their rapid development, high target specificity, and the capacity to increase druggability. Here, we review key anti-CoV NA-based te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 98 publications
1
49
0
1
Order By: Relevance
“…Similarly, hybridization-guided therapeutics, such as antisense oligonucleotides, small interfering RNAs, and CRISPR-derived drugs could potentially be targeted to the SARS-CoV-2 genome. 41 Unstructured regions in noncoding regions of the viral genome make particularly compelling targets, as access will not be blocked by RNA structure or transit of the ribosome. However, because these strategies rely on base complementarity to achieve target specificity, rapid virus evolution could prove their Achilles’ heel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, hybridization-guided therapeutics, such as antisense oligonucleotides, small interfering RNAs, and CRISPR-derived drugs could potentially be targeted to the SARS-CoV-2 genome. 41 Unstructured regions in noncoding regions of the viral genome make particularly compelling targets, as access will not be blocked by RNA structure or transit of the ribosome. However, because these strategies rely on base complementarity to achieve target specificity, rapid virus evolution could prove their Achilles’ heel.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 There is also interest in targeting the viral genome directly, using compounds that target conserved RNA structures such as the frame-shifting pseudoknot, 39 , 40 or using informational drugs such as RNA interference triggers or antisense oligonucleotides that directly recognize the viral genome sequence. 41 As such, it is critically important that we understand how sequence and structure of viral cis-regulatory elements changes as the virus spreads. This understanding will help guide new therapeutic development to the most conserved sequences and structures, limiting the opportunity for the emergence of resistant variants in the future.…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have revealed that lncRNAs have a wide range of regulatory functions in obesity-related adipogenesis and lipid metabolism [28,29]. On the one hand, lncRNA that plays a key regulatory role in adipogenic differentiation can be used as a diagnostic marker for obesity prevention as most of the previous application cases [30][31][32]; on the other hand, although the effect of inhibiting MSC adipogenic differentiation on existing obesity remains to be clarified, whether the ASO [33,34] targeting lncRNA can be developed and utilized to intervene in obesity or at least prevent more serious obesity is still worth further study. However, most current researches based on mousederived cells or cell lines, but lncRNAs have poor conservation across species, which appears to be an inescapable barrier for comprehensively understanding the development of human adipose and future clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their safety, tolerance, and high potency have been demonstrated in numerous studies. [ 350 ] Karikó et al laid the foundation for RNA‐based vaccines in 2008. [ 351 ] In their research, the authors demonstrated that the nucleoside‐modified mRNA (modRNA) containing pseudouridines is translated more efficiently than unmodified mRNA in vitro, particularly in primary mammalian dendritic cells and in vivo in mice.…”
Section: Rna Delivery Applicationsmentioning
confidence: 99%